Learning motivation and strategies of ESP university students - Joseba M. González Ardeo (Revista de Lenguas para Fines Específicos, 2016)
This paper deals with two of the key factors in the L2 learning process, namely, learning motivation and strategies. A group of engineering students from Bilbao (Spain) having a good command of English for General Purposes (EGP) and taking a course in English for Specific Purposes (ESP) are the basis of a study in which types of English Learning Motivation (ELM), i.e. intrinsic and extrinsic (integrative and instrumental) (Brown, 2000), and types of English Learning Strategies (ELSs), i.e. memory, cognitive, compensation, metacognitive, affective and social strategies (Oxford, 1990), are analysed. As expected, Instrumental ELM and Cognitive and Metacognitive ELSs are the most widely used by these learners. However, some striking and significant differences appear in connection with: 1) male vs female Intrinsic ELM and Social ELSs; 2) 21-23 vs 24-27 age group Instrumental (EGP) ELM, and Metacognitive and Social ELSs. Finally, with respect to the prospective correlation between ELM and ELS types, the results seem to confirm that there are signicant correlations among most of them; e.g., Instrumental (ESP) ELM is positively and significantly correlated with all but Affective ELM.